2019
DOI: 10.1002/fsn3.1209
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of rapeseed cake oil using subcritical R134a/butane: Process optimization and quality evaluation

Abstract: The optimal extraction conditions of rapeseed cake oil using subcritical R134a/butane were established by response surface methodology. The quality of subcritical R134a/butane extraction oil (SRBEO) was compared with supercritical CO2 extraction oil (SCO2EO) and hexane extraction oil (HXEO). The results showed the highest extraction yield obtained by subcritical R134a/butane in the condition of R134a‐butane ratio of 1.5 kg/kg, at 45°C for 50 min. Compared with SCO2EO and HXEO, the extraction yield and β‐carote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Phytosterols are the principal constituent of unsaponifiable matter, which can reduce the level of plasma cholesterols and the incidence of heart disease and cancer 33 . Table 4 shows that four types of phytosterols were identified from the flaxseed oils extracted with three different methods.…”
Section: Content Of Carotenoid and Phytosterolsmentioning
confidence: 99%
“…Phytosterols are the principal constituent of unsaponifiable matter, which can reduce the level of plasma cholesterols and the incidence of heart disease and cancer 33 . Table 4 shows that four types of phytosterols were identified from the flaxseed oils extracted with three different methods.…”
Section: Content Of Carotenoid and Phytosterolsmentioning
confidence: 99%
“…Although SUBLDME is wildly used for the extraction of biologically active, lipid, flavoring, or pungent organic compounds in many substances, there are not many studies investigating the effect of the extraction on RBO and phytosterol content. Kamchonemenukool et al [ 101 ] found high phytosterol contents from filter mud discarded from sugar mill extracted using SUBLDME at 20,879 mg/100 g. Guo et al [ 45 ] also reported the phytosterol content of rapeseed cake oil extracted with subcritical 1,1,1,2-tetrafluoroethane (R134a)/butane was 560.19 mg/100 g. Zanqui et al [ 102 ] extracted Brazil nut oil with subcritical n-propane by varying the extraction temperature and pressure, and obtained phytosterol contents ranging from 54.09 to 69.99 mg/100 g. Han et al [ 103 ] also found the phytosterol content of soybean germ oil extracted with subcritical butane at 2772.90 mg/100 g.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, especially oils from regionally produced raw materials are hard to be expected. Nevertheless, the pre‐treatment of rapeseed and the method by which rapeseed oil is extracted from the press cake can influence its quality (Guo et al., 2019; Yu et al., 2020; Zhou et al., 2019). There were indications that the pre‐treatment of rapeseed by steam explosion led to a better oil quality as compared to the traditional high‐temperature roasting (Yu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There were indications that the pre‐treatment of rapeseed by steam explosion led to a better oil quality as compared to the traditional high‐temperature roasting (Yu et al., 2020). In addition, it was shown that the use of butane as an extraction agent increased the extracted oil yield and the concentrations of ß‐carotene, tocopherol, and canolol in the oil and slightly reduced the erucic acid concentrations (Guo et al., 2019).…”
Section: Discussionmentioning
confidence: 99%